Kultura i globalna róŜnorodność kreatywna - Sikorska, Joanna (Studia Edukacyjne, 2020)
The idea that different cultures think differently about cultural aspects of education is clearly seen in Cyberspace, where people converge, discuss and apply new ideas to the educational programs in their home countries. It is because of Cyberspace that our ideas pertaining to culture education changed or shifted from their axis. Cyberspace continues to grow and the growth triggers problems, which is normal considering it is a place where many cultures interact with each other. As pedagogues and teachers, we should counteract cyberbullying and cyberstalking in Cyberspace and prevent such things from happening in real life. In my opinion, everyone should learn the culture of his/her home country and countries he/she will someday come into contact with. We cannot continue to be blinded by what others say, we need to educate children so that we can be proud of them further down the line. Otherwise children will educate themselves and that can contribute to hate, misunderstandings, prejudice, and anger towards people from other cultures. This paper will give examples of the diversity of cultures comprising our world and try to show how we can protect and help children by listening to them so that they can understand this diversity, and allow them to be the creators of their own future, which would not be based on prejudice and stereotype.